Windows Phone 7 Recipes A Problem-Solution Approach - Ferracchiati, Fabio Claudio; Garofalo, Emanuele; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2011)
Developers are racing to discover how todevelop for Windows Phone 7$1 (Band there is no quicker resource to help you get upto speed than Windows Phone 7 Recipes.This book covers all aspects of development, configuration, testing, anddistribution, with detailed code samples and rapid walkthroughs to support youevery step of the way. You'll find recipes that unlock advanceduser interface development, data storage and retrieval, integration with cloudservices, adding media and location-based services, and working withSilverlight and Expression Blend. Learn to use sensors such as thecamera, GPS, and accelerometer to build cutting-edgeapplications. Manage the new way to interact with applications using the gestureslibrary both from the XNA Framework library and the Silverlight Windows PhoneToolkit library.s
Keywords: Computer science; Computer Science; Computer Science, general